Innovation in Science Learning Using Augmented Reality in Animal Metamorphosis Materials - Rafika Widiastuti; Hestina Nur Rahmawati; Ayu Nimas Puspaningrum; Aura Suci Adillah Nur Aisyah; Khafidz Akmal Assidqi (Journal of Software Engineering, Information and Communication Technology (SEICT), 2022)
Currently, there are still many science lessons that use the lecture method and are teacher-centred. There are still many students' natural science scores whose grades are below the KKM; the cause of low grades in this era is monotonous and unpleasant learning. Teacher-centred learning also makes students easily bored and bored, so they are not interested in learning related to the material being presented. Regarding this problem, the authors created a learning media in the form of an augmented reality application that functions to help students get to know and interact in real-time about Natural Sciences subjects, especially on animal metamorphosis material. The author uses the Multimedia Development Life Cycle (MDLC) development model through six stages, namely concept, design, collecting, assembly, testing, and distribution. From the results of making this application, animal metamorphosis learning will be easily recognized through augmented reality media, and students can enthusiastically learn using this application. Therefore, it is essential to make this learning media because students will be interested in learning new things, primarily related to 3D from augmented reality. Moreover, this technology is still rarely encountered and used in learning today.